The man everyone hated: José María Gil-Robles and the Spanish Civil War - Rodríguez López-Brea, Carlos (Hispania Nova, 2021)
This article analyzes the process of harassment and demolition suffered by the leader of the CEDA, José María Gil-Robles during the Spanish Civil War. The first part studies the responsibility of this political leader in the coup of 1936, which he joined with the hope of taking power in the medium term. Things did not go as expected and his figure suffered a deep wear on both sides of the fight. After July 18, the Republicans saw confirmed the old suspicion that Gil-Robles was a conspirator who wanted to overthrow democracy by force, while in the so-called National Spain, where the Falange took control of the propaganda, the CEDA and its “Jefe” symbolized the old politics that Falangism was supposed to destroy.
Keywords: Spanish Civil War; Gil-Robles; political catholicism; Franco; press